SEOM clinical guidelines for the treatment of renal cell carcinoma - Bellmunt, J. (Clin Transl Oncol, 2014)
The purpose of this article was to provide updated recommendations for the diagnosis and treatment of renal cell carcinoma. Pathological confirmation is mandatory before treatment with ablative or focal therapies before any type of systemic therapy. Renal cell cancer should be staged according to the TNM classification system. A laparoscopic nephron-sparing surgery should be the approach for tumors <4 cm if technically feasible. Otherwise, radical (or partial in selected cases) nephrectomy is the treatment of choice, with lymph node dissection only performed in patients with clinically detected lymph node involvement. Some retrospective evidence for a cytoreductive nephrectomy in the postimmunotherapy era suggests a benefit in patients with good or intermediate risk or for patients with a symptomatic primary lesion. Adjuvant treatment with chemotherapy or with targeted agents is not recommended and studies are ongoing today. Patients with metastatic disease should be staged by computed tomography scans of the chest, abdomen and pelvis. The efficacy of sunitinib, bevacizumab plus interferon-α, and pazopanib is well established in patients with good and intermediate risk as well for temsirolimus in poor-risk patients. These four agents are considered standard of care in first-line treatment. Sorafenib, axitinib and everolimus are standard of care in second line in different settings based on their benefit in PFS. Besides some benefit described for IL-2 in highly selected patients in first line, there is a promising and emerging role for the new immunotherapeutic approaches in metastatic renal cell carcinoma.